School days - Parker, Robert B., 1932-2010 (No Exit Press, 2006)
Two students in ski masks execute seven people at Dowling Academy before one of them, Wendell Grant, surrenders to police.The authorities are convinced the other perpetrator was Jared Clark.Clark's grandmother Lily Ellsworth is the grand dame of Dowling, Massachusetts, and possesses an iron will and bottomless purse. When she hires Spenser to investigate her grandson's alleged involvement in the school shooting, the P.l. is led into an investigation that grows more harrowing at every turn: the boy himself seems indifferent to his own fate, and the school officials don't want the detective on the case.But as he digs further Spenser uncovers a web of blackmail and some heavy-duty indiscretions, and, before the case reaches its unfortunate end, a truth too disturbing to contemplate.